سلطنتِ عثمانیہ اور قانونِ برادرکشی :فوائد و نقصانات: The Ottoman Empire and the Law of Fratricide: Pros and Cons (Al-Qamar, 2023)
Undoubtedly, fratricide is one of the most controversial topics of Ottoman history. Although this practice was not new in the history of kingdoms. But the king Mehmed II, the conqueror’s law about secure governance imparted that in exercising of Hakuk 'Urfi' a sultan may kill his brothers for sheltered Government. One may find different reasons for fratricide in Ottoman Era considering most of them as legitimate. Some executions were acted to stop a possible revolt, and were criticized as illegitimate.  Some of the Ottoman ʻUlamāʻ approved its legitimacy by regarding fratricide as a precaution due to the Maslahah principle, not as a punishment. Beside this they introduced some Quranic verses as evidence in order to support their opinion. Later on, Sultan Ahmed I ended this custom and introduced the system of seniority succession instead off arcticid. Although it seems prudent and scrupulously convenient but this practice handicapped the empire and proved a major reason to end the empire in stagnation period. But we see the region remained strengthened when the fratricide was Premi leant and the abandonment of fratricide proved one reason among the others, a cause of fall of Ottoman Empire.
Keywords: Ottoman Empire; Fratricide; Fall of Ottoman Empire; prose and cons